The secret history: A Novel - Tartt, Donna (New York : Vintage Books, 2004)
Richard Papen had never been to New England before his nineteenth year. Then he arrived at Hampeden College and quickly became seduced by the sweet, dark rhythms of campus life -- in particular by an elite group of five students, Greek scholars, worldly, self-assured, and at first glance, highly unapproachable.
new book 2023 winter.
Keywords: Teacher-student relationships -- Fiction; College students -- Fiction; Classicists -- Fiction; Murder -- Fiction; Papen, Richard (Fictitious character) -- Fiction; Vermont -- Fiction; College stories; Psychological fiction